(untitled) (Malaysian Journal of Learning and Instruction, 2004)
This study looks at how instructors perceive sexism and respond to the portrayal of gender in a textbook. A total of six instructors of an institution of higher learning were interviewed. These instructors were asked three basic questions: (1) Do you discuss gender issues in the classroom? (2) Were you aware of the gender stereotypes in the textbook? (3) How are you going to respond to gender stereotypes in the textbook after being aware? Findings indicate that the instructors did not intend to discuss gender in the classroom. Discussions on gender would be incidental, depending on the topic of the units covered in the textbook. In addition, the instructors did not discuss gender because they had not been aware of gender stereotypes in the textbook. However; most of them felt reluctant to discuss issues on gender even after they were made aware of gender stereotypes in the textbook. Reasons for this include time constraints in completing the syllabus, students’ level of proficiency and students’ awareness of gender issues. The avoidance of discussions on gender issues was also due to two main reasons: one, gender issues were not part of the syllabus to be covered and two, these issues were not part of the local culture. It is suggested that the instructors should attempt to discuss gender stereotypes and the idea of equality among gender in the classroom, especially if sexism existed in the textbook, to avoid gender stereotypes being part of the hidden curriculum.